Encyclopedia of Life Sciences 2015
DOI: 10.1002/9780470015902.a0025962
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriophages and Food Safety

Abstract: Interest in using bacteriophages to improve food safety has been gaining momentum recently, driven by both the continued occurrence of foodborne outbreaks worldwide and the desire of consumers for natural foods. Bacteriophages are naturally part of the normal microflora of many foods, and the ‘phage biocontrol’ approach is based on the concept of using the right phage, in the right place, in the right concentration to control foodborne pathogens. This approach has been applied to three main areas of food safet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…Lytic bacteriophages are becoming increasingly utilized for improving the safety of human food supply, yet their application in the pet food industry is still very limited (reviewed in 14,16 ). In a previous study, we reported the application of the same Salmonella phage preparation significantly reduced Salmonella contamination of dry pet food.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lytic bacteriophages are becoming increasingly utilized for improving the safety of human food supply, yet their application in the pet food industry is still very limited (reviewed in 14,16 ). In a previous study, we reported the application of the same Salmonella phage preparation significantly reduced Salmonella contamination of dry pet food.…”
Section: Discussionmentioning
confidence: 99%
“…14 SalmoLyse Ò is composed of 6 lytic phages effective against Salmonella strains belonging to some of the most common and highly pathogenic serotypes, including Typhimurium, Enteritidis, Heidelberg, Newport, Hadar, Kentucky, Thompson, Georgia, Agona, Grampian, Senftenberg, Alachua, Infantis, Reading, and Schwarzengrund. 14,15 During previous studies, SalmoLyse reduced Salmonella by ca. 1 log in dry kibble.…”
Section: Introductionmentioning
confidence: 97%
“…coli O157:H7, and Salmonella are currently on the market. These preparations offer safe and effective intervention modalities for removing their targeted bacteria from various foods, without altering organoleptic qualities of those foods and their normal microflora / nutritional characteristics [16]. After ShigaShield ™ becomes commercially available, it will be another addition to that growing family of all natural lytic phage preparations that can serve as an important additional tool for reducing the levels of Shigella in our foods and making them safer to eat.…”
Section: Resultsmentioning
confidence: 99%
“…Lytic phages have a potent, highly specific bactericidal activity against their targeted bacterial cells–a feature that enables a targeted killing of specific problem-causing bacteria in various settings, without disturbing the normal–and often beneficial–microflora. Various bacteriophage-based food additives have been approved by the FDA for food safety applications, including (listed in chronological order of receipt of regulatory approval in the USA): ListShield ™ , Listex P-100 ™ , EcoShield ™ , SalmoFresh ™ and Salmonelex ™ [16]. Here, we report the results of studies in which the ability of ShigaShield ™ to reduce Shigella levels was evaluated in various foods experimentally contaminated with a S .…”
Section: Introductionmentioning
confidence: 99%
“…Bacteriophage biocontrol could also be a means to disinfect surfaces used in the production and processing of foods [ 16 , 17 ]. In previous reviews [ 12 , 14 , 18 , 19 ], we and others have assembled a general overview of the industries and products where bacteriophages are used in food safety applications. Here, we provide an updated review (and an extended summary table) describing studies where bacteriophages have been applied to predominantly post-harvest foods, particularly meats, fresh produce and RTE foods ( Table 1 ).…”
Section: Introductionmentioning
confidence: 99%